2006
DOI: 10.2174/138945006776055004
|View full text |Cite
|
Sign up to set email alerts
|

Natural Flavonoids Targeting Deregulated Cell Cycle Progression in Cancer Cells

Abstract: The prolonged duration requiring alteration of multi-genetic and epigenetic molecular events for cancer development provides a strong rationale for cancer prevention, which is developing as a potential strategy to arrest or reverse carcinogenic changes before the appearance of the malignant disease. Cell cycle progression is an important biological event having controlled regulation in normal cells, which almost universally becomes aberrant or deregulated in transformed and neoplastic cells. In this regard, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 77 publications
(144 reference statements)
1
78
0
Order By: Relevance
“…28,30 The flavonoids also modulated the several proteins that involved in cancer promotion for instance protein kinases, epidermal growth factor receptors, platelet derived growth factor receptors, vascular endothelial growth factor receptors and cyclin-dependent kinases. 28,31 As shown in Figure 4, group A has the highest level of phenolics, while group Chas the lowest level. Group B showed medium phenolic content compared with other groups.…”
Section: Discussionmentioning
confidence: 95%
“…28,30 The flavonoids also modulated the several proteins that involved in cancer promotion for instance protein kinases, epidermal growth factor receptors, platelet derived growth factor receptors, vascular endothelial growth factor receptors and cyclin-dependent kinases. 28,31 As shown in Figure 4, group A has the highest level of phenolics, while group Chas the lowest level. Group B showed medium phenolic content compared with other groups.…”
Section: Discussionmentioning
confidence: 95%
“…Several lines of evidence indicate that ROS may be involved in human carcinogenesis: (a) some growth factors such as epidermal growth factor (EGF), insulin, and angiopoietin-1 increase ROS production in the cells for regulating cell migration and proliferation (3)(4)(5)(6); (b) natural antioxidants can inhibit cancer cell proliferation and tumor growth (7)(8)(9)(10); (c) high levels of ROS are observed in some cancer cells, which may induce DNA damage leading to genomic instability and tumor initiation (11,12); and (d) ROS induce the activation of mitogen-activated protein (MAP) kinase, nuclear factor nB (NF-nB), and activator protein 1, which are known to be associated with cancer development (13)(14)(15). However, under certain conditions, ROS increase proapoptotic molecules such as p53 and p38 MAP kinase and induce cellular apoptosis (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that there is a relationship between higher kava consumption and lower incidence of cancer (Steiner 2000;Sarris and Kavanagh 2009). Flavonoids synthesized from chalcone precursors, isolated from plants, have antiproliferative activities with therapeutic potential, while the chalcone flavokawain from medicinal plants is as one of the best-selling medicinal foods in European and American markets (Lebot et al 1992;Go et al 2005;Singh and Agarwal 2006). Flavokawain A, B, and C, constitute approximately 0.46%, 0.015%, and 0.012% of kava extracts, respectively (Dharmaratne et al 2002).…”
Section: Introductionmentioning
confidence: 99%